The Metabolic and Neurochemical Etiopathology of Passive Exposition to Alcohol Consumers - Lamothe Nery; Lamothe Mara; Lamothe Daniel; Villanueva Ernesto; Bueno Pilar; Alonso-Altamirano Alejandro; Clemente-Herrera Adriana; Hernández Estuardo; Guillermo Castillo-Vázquez Francisco; Gerardo Roche Andrės (Journal of Public Health International, 2021)
A narrative review considers metabolic and neurochemical pathways implicated in passive exposure to alcohol consumers, discussing health effects and research needs.
Keywords: Passive Health Victims